Peripheral Blood and Cerebrospinal Fluid Cytokine Levels in Guillain Barré Syndrome: A Systematic Review and Meta-Analysis - Sun, Ting; Chen, Xi; Shi, Sha; Liu, Qingshan; Cheng, Yong (Frontiers in Neuroscience, 2019)
Guillain Barré Syndrome (GBS) is an autoimmune disorder caused by the immune system damaging the peripheral nervous system. Increasing evidence suggest that inflammatory cytokines are important mediators for the onset and progression of GBS. A number of clinical studies have demonstrated elevated levels of Th1, Th2 and Th17 related cytokines in the patients with GBS, but results were inconsistent across studies. Therefore, we performed a systematic review and meta-analysis of studies comparing cerebrospinal fluid and peripheral blood inflammatory cytokine levels between the patients with GBS and healthy individuals. The database search identified 30 studies encompassing 1302 GBS patients and 1073 controls to be included. The random-effects meta-analysis demonstrated that blood tumor necrosis factor-ɑ (Hedges g,1.544; 95% CI, 0.923-2.165; p < 0.001), interleukin-1β (IL-1β; Hedges g, 0.678; 95% CI, 0.183-1.172; p = 0.007), IL-6 (Hedges g, 0.630; 95% CI, 0.100 -1.160; p = 0.02), IL-4 (Hedges g, 0.822; 95% CI, 0.220-1.423; p = 0.007 ), IL-17 (Hedges g, 1.452; 95% CI, 0.331-2.573; p = 0.011), interferon-γ (Hedges g,1.104; 95% CI, 0.490-1.719; p < 0.001) and C-reactive protein (Hedges g, 0.909; 95% CI, 0.453-1.365; p < 0.001) levels were significantly increased in the patients with GBS when compared with controls. In contrast, the blood IL-10 and TGF-β levels were not significantly associated with GBS. Furthermore, the meta-analysis found that cerebrospinal fluid IL-17 levels were significantly associated with GBS (Hedges g, 1.882; 95% CI, 0.104-3.661; p = 0.038). Taken together, our results clarified the circulating inflammatory cytokine profile in the patients with GBS, and revealed that Th1, Th2 and Th17 related cytokines were highly elevated in the GBS patients, and suggesting the potential of these cytokines to be used as biomarkers for GBS.